Effect of pimobendan on TAPSE in dogs with cardiac valvular disease - Gonul, R; Seddigh Nia, A (Journal of the Hellenic Veterinary Medical Society, 2024)
Many caridac and pulmonary disease affect right heart functions. Therefore, clinical examination of it’s systolic function has recently became important in humans, whereas it has been largely overlooked in dogs. So that in this research, the effects of pimobendan on right ventricular fractional area change (RVFAC), tricuspid annular plane systolic excursion (TAPSE), and systolic functions were analyzed in detail by echocardiography. For this purpose, 40 cases of mitral and/or tricuspid valve disease (group II) and 10 healthy dogs (group I) were included in the study. Echocardiographic examinations were repeated after giving of pimobendan (0.2 mg/kg x2 for 1 week) (group III). In the echocardiographic examinations, the values EF, EPSS, RV area (D), RV area (S), IVSd, IVSs, LVPWs, MV E, and MV A showed statistically significant differences between the groups. Also, we found that TAPSE was lower in group II (1.29) than in group I (2.25) (P<0.001), and after treatment with pimobendan, TAPSE was increased (1.41). RVFAC also decreased in the patient group, and this value increased after treatment with pimobendan, as did TAPSE, but these changes weren't statistically significant. Therefore, we concluded that right ventricular functions should be carefully monitored in patients with various heart diseases for better diagnosis, treatment, and prognosis.